Handbook of Canadian Foreign Policy - James, Patrick; Michaud, Nelson; O'Reilly, Marc (Lexington Books, 2006)
Handbook of Canadian Foreign Policy is the most comprehensive book of its kind, offering an updated examination of Canada's international role some 15 years after the dismantling of the Berlin Wall ushered in a new era in world politics. Tackling recent developments in Canadian foreign policy, the authors of this work spotlight Canadian idiosyncrasies within a global context that are defined by wrenching juxtapositions. The specialists who have contributed their expertise to this book provide sophisticated analysis-conceptual as well as historical-rather than simply impressionistic judgments about contemporary events. Highlighting both well-known and understudied topics, this handbook presents a marriage of the familiar and the underappreciated that enables readers to grasp much of the complexity of current Canadian foreign policy and appreciate the challenges policymakers must meet in the early 21st century.